Pemberian Edukasi Mengenai Pola Makan Sehat Pada Siswa-Siswi SMP Negeri 5 Sambas - Syahrulizar Arditiya; Abdul Karim; Crisna Aprilia; Dian Hardiyanti; Erdiana Laura; Hesty Sulistiya; Khofifah; Muniza (PPPM POLITEKNIK NEGERI SAMBAS, 2022)
In this day and age, ready-to-eat food is more attractive to teenagers because it is easy and short to serve. Fast food is considered contemporary food and is popular among teenagers. Teenagers need to get used to a healthy diet to build a body. Therefore, counseling was carried out with the aim of providing learning about healthy eating patterns to seventh and eighth grade students. This activity was carried out at SMP Negeri 5 Sambas on June 9, 2022 in the form of counseling with the theme